Targeting of cathepsin S reduces cystic fibrosis-like lung disease - Small, Donna M.; Brown, Ryan; Zhou-Suckow, Zhe; Mall, Marcus A. (The European respiratory journal, 2019)
Cathepsin S (CatS) is upregulated in the lungs of patients with cystic fibrosis (CF). However, its role in CF lung disease pathogenesis remains unclear. - In this study, β-epithelial Na+ channel-overexpressing transgenic (βENaC-Tg) mice, a model of CF-like lung disease, were crossed with CatS null (CatS−/−) mice or treated with the CatS inhibitor VBY-999. - Levels of active CatS were elevated in the lungs of βENaC-Tg mice compared with wild-type (WT) littermates. CatS−/−βENaC-Tg mice exhibited decreased pulmonary inflammation, mucus obstruction and structural lung damage compared with βENaC-Tg mice. Pharmacological inhibition of CatS resulted in a significant decrease in pulmonary inflammation, lung damage and mucus plugging in the lungs of βENaC-Tg mice. In addition, instillation of CatS into the lungs of WT mice resulted in inflammation, lung remodelling and upregulation of mucin expression. Inhibition of the CatS target, protease-activated receptor 2 (PAR2), in βENaC-Tg mice resulted in a reduction in airway inflammation and mucin expression, indicating a role for this receptor in CatS-induced lung pathology. - Our data indicate an important role for CatS in the pathogenesis of CF-like lung disease mediated in part by PAR2 and highlight CatS as a therapeutic target. - Tweetable abstract ERSpublications - click to tweetCathepsin S is involved in inflammation, mucus production and lung tissue damage in a model of CF-like lung disease http://ow.ly/tHcm30nhlcX